2002
DOI: 10.1073/pnas.122187699
|View full text |Cite
|
Sign up to set email alerts
|

The endocytic catalysts, Rab5a and Rab7, are tandem regulators of thyroid hormone production

Abstract: Rab proteins are small GTPases that control distinct vesicular transport steps. Along the endocytic pathway, Rab5a is a ratelimiting catalyst of internalization, and Rab7 controls trafficking through late endosomes to lysosomes. The dependence of thyroid hormone production by thyrocytes on thyroglobulin endocytosis and intracellular processing in late endosomes͞lysosomes suggests that its rate can be regulated by the expression or function of these endocytic catalysts. We compared the expression level and memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 43 publications
1
70
0
Order By: Relevance
“…Finally, we found that our ATC/PDTC series had a deregulation of critical genes for thyroid hormone synthesis, such as the overexpression of ARRB2 (b-arrestin 2; Voigt et al, 2000), which is implicated in the desensitization of thyroid-stimulating hormone receptors (TSHR), the underexpression of RAB5A, which participates in the thyroglobulin production (TG; Croizet-Berger et al, 2002), and a diminished expression of TG and PAX8, which has also been observed before in ATC/PDTC series (Onda et al, 2004). Furthermore, the expression of HHEX, a gene related to thyroid morphogenesis and differentiation, was decreased in ATC/PDTC.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, we found that our ATC/PDTC series had a deregulation of critical genes for thyroid hormone synthesis, such as the overexpression of ARRB2 (b-arrestin 2; Voigt et al, 2000), which is implicated in the desensitization of thyroid-stimulating hormone receptors (TSHR), the underexpression of RAB5A, which participates in the thyroglobulin production (TG; Croizet-Berger et al, 2002), and a diminished expression of TG and PAX8, which has also been observed before in ATC/PDTC series (Onda et al, 2004). Furthermore, the expression of HHEX, a gene related to thyroid morphogenesis and differentiation, was decreased in ATC/PDTC.…”
Section: Discussionmentioning
confidence: 98%
“…Rab GTPases regulate tumorigenesis via trafficking-mediated events, and some function in a trafficking-independent manner [22,[37][38][39][40]. Additionally, it is known that several members of the Rab GTPase family affect exosome secretion via the trans-Golgi network or by inducible vesicular trafficking [35,41].…”
Section: Discussionmentioning
confidence: 99%
“…We have shown an increase in RAB25 gene expression in ovarian and breast cancers. Increased RAB25 levels have also been noted in prostate cancer (23), transitional cell carcinoma of the bladder (24), and invasive breast tumor cells (25), suggesting the pathologic role of RAB proteins in the development or progression of tumors in multiple epithelial lineages.…”
Section: Intercellular Vesicle Trafficking Pathways: a Potential Thermentioning
confidence: 99%